To what extent are students' self-perceived ICT interest, competence and autonomy associated with achievement? - Gill, C. M. H. D.*; Berezina, Elizaveta * (ACM Digital Library, 2022)
Information and communications technology (ICT) is now extensively used in educational settings and its use has increased since the onset of the pandemic. However, since the first use of computers in classrooms nearly 50 years ago, the evidence for the impact of ICT on student achievement has been contradictory. Some researchers have suggested that access to high quality ICT, and familiarity and competence in the use of ICT are associated with higher student attainment, whereas others have contended the opposite. However, it has been suggested that positive attitudes to ICT may generalize to positivity toward disciplines taught using ICT. The present research empirically investigates the associations between student attainment, students’ access to ICT, use of ICT in schools, and students’ perceived interest, competence and autonomy in the use of ICT, using samples drawn from the PISA 2018 data for Hong Kong Special Administrative Region, Japan and Republic of Korea. Use of ICT at home and in school was found to be consistently negatively associated with student attainment, but access to ICT resources was positively associated with attainment in two of the three jurisdictions. Students’ perception of their own competence using ICT was negatively associated with attainment in Republic of Korea, but had no significant associations in the other territories. Self-reported interest in ICT and autonomous use of ICT were both positive associated with student achievement. This suggests that student perceptions of ICT may be more important than ICT itself in raising levels of student attainment.